Civil insurgency and intelligence operations - Girish Bihari (New Delhi, 1982)
This book attempts to clarify, codify and crystalise this fascinating and complex subject. Tracing the concept of guerrilla warfare from the dawn of history, the author defines lucidly its starategy, tactics and principles and misconceptions.
Keywords: Insurgency India